2017
DOI: 10.1007/s10753-017-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Fatty Acid Increases Lung Macrophages and Augments House Dust Mite-Induced Airway Inflammation in Mice Fed with High-Fat Diet

Abstract: Obesity is one of the phenotypes of severe asthma, which is considered to be a heterogeneous syndrome; however, its interaction with airway inflammation is not fully understood. The aim of this study was to clarify the role of saturated fatty acids in augmenting airway inflammation induced by house dust mite (HDM) in obesity. Subjects were Balb/c mice fed a high-fat diet (HFD) for 10 weeks, followed by sensitization and exposure to HDM. Subjects were also administered palmitic acid (PA) for 4 weeks with concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 53 publications
4
53
1
Order By: Relevance
“…IL-33 from monocytes recruited to the lung contributes to the pathogenesis of HDM-induced airway inflammation [12]. Saturated fatty acids increase the recruitment of lung macrophages and augments HDM-induced airway inflammation in obese mice [47]. In the present study, the number of interstitial macrophages (defined as CD45 + , CD11c low , CD11b + , and Ly6c − cells) was significantly decreased with EM900 or CAM treatment in HDM and poly(I:C)-induced airway inflammation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 from monocytes recruited to the lung contributes to the pathogenesis of HDM-induced airway inflammation [12]. Saturated fatty acids increase the recruitment of lung macrophages and augments HDM-induced airway inflammation in obese mice [47]. In the present study, the number of interstitial macrophages (defined as CD45 + , CD11c low , CD11b + , and Ly6c − cells) was significantly decreased with EM900 or CAM treatment in HDM and poly(I:C)-induced airway inflammation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…These authors and others (50) also reported greater sputum IL-17A, a cytokine important for neutrophil recruitment, in the obese than the lean patients suggesting that this cytokine may be contributing the neutrophil recruitment in these patients. Data from animal models also suggest a link between IL-17A and obese asthma (51). Obese mice typically exhibit innate airway hyperresponsiveness, but this hyperresponsiveness is not observed if the animals are IL-17A deficient (52).…”
Section: Obesity Increases the Severity Of Asthmamentioning
confidence: 99%
“…This triggers activation of canonical inflammatory signaling pathways that produce proinflammatory mediators and other effectors of the innate immune system (Rogero and Calder, 2018). Furthermore, consumption of a HFD in mice increased macrophage infiltration to lung tissue, specifically in the alveoli (Tashiro et al, 2017). This is especially relevant to COVID-19 patients given the high rate of infection among lung alveolar epithelial cells and the involvement of lung tissue inflammation and alveolar damage in COVID-19 pathology (Xu et al, 2020).…”
mentioning
confidence: 99%